Electronic spectral and photophysical properties of some p-phenylenevinylene oligomers in solution and thin films - Melo, J. Seixas de (2006)
A comprehensive photophysical and spectroscopic study of a new class of p-phenylenevinylene oligomers (PPV-trimers) possessing different alkyl and alkyloxy sidechain substituents and different end groups (aldehyde, CC, phenylene and anthracene units) was undertaken in solution at room temperature (293 K), low temperature (77 K) and in thin films. The study comprises absorption, emission and triplet-triplet absorption spectra, together with quantitative measurements of quantum yields (fluorescence, intersystem crossing, internal conversion and singlet oxygen formation) and lifetimes. The data allow the determination of rate constants for all decay processes. From these, several conclusions could be drawn. Changing from alkyl to alkyloxy substituents does not change fluorescence and internal conversion yields but decreases the (already small) intersystem crossing yield. The introduction of anthracene at the terminal ends of the PPV-trimers leads to the lowest fluorescence yield reported in this study. Of particular importance is the fact that the fluorescence quantum yields in films are of the same order of magnitude as those in solution, which suggests the potential for use of these oligomers for light-emitting device applications. With one of the alkyloxy derivatives, a more detailed study of the early part of the fluorescence decay was made, and it was found that upon excitation a fast conformational relaxation process of the initially excited oligomer occurs, leading to a more planar conjugation segment.